Soluble mediators in the function of the epidermal-immune-neuro unit in the skin - Oleszycka, Ewa; Kwiecien, Kamila; Kwiecinska, Patrycja; Morytko, Agnieszka; Pocalun, Natalia; Camacho, Michelle; Brzoza, Piotr; Zabel, Brian A.; Cichy, Joanna (Frontiers in Immunology, 2022)
Skin is the largest, environmentally exposed (barrier) organ, capable of integrating various signals into effective defensive responses. The functional significance of interactions among the epidermis and the immune and nervous systems in regulating and maintaining skin barrier function is only now becoming recognized in relation to skin pathophysiology. This review focuses on newly described pathways that involve soluble mediator-mediated crosstalk between these compartments. Dysregulation of these connections can lead to chronic inflammatory diseases and/or pathologic conditions associated with chronic pain or itch.